Grand Design of Values Education Approach and Strategy for the Golden Generation - Nisak, Sayida Khoiratun; Susanto, Ilham Arya; Arzuna, Pit; Wulandari, Triyana; Hidayat, Wildan Nur (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
Effective character education for the younger generation is crucial in facing global challenges in the future. By integrating local and global values, education can shape students who not only understand their cultural roots but are also ready to contribute positively to the global community. This study aims to explore innovative approaches in character education that combine local and global values to form a competent generation. The method used is a literature review, examining various educational strategies such as project-based learning, service learning, arts-based education, and technology. The results of the study show that the synergy between local and global values in education helps students develop social skills, empathy, and social justice. Additionally, this approach also prepares students to collaborate internationally, develop critical and creative thinking skills, and build adaptable character traits, making them ready to become responsible future leaders. Integrating these values in education will ensure a competent, open-minded, and globally prepared younger generation.